Comparative Study of the Adverse Events Associated With Adjuvant Use of Dexmedetomidine and Clonidine in Local Anesthesia - Jiang, Jinjin; Shen, Huasu; Zhang, Jin; Wu, Zhen; Shao, Xian; Cui, Jingjing; Zhang, Bao; Ma, Xiaoyu (Frontiers in Medicine, 2021)
Background: Although clonidine and dexmedetomidine used as alpha-2 agonists to improve the quality and duration of blockade induced by local anesthetics, no study has been reported to compare their associated adverse events in local anesthesia. The aim of this study is to compare the adverse events associated with the adjuvant use of dexmedetomidine and clonidine in local anesthesia. Methods: A comprehensive search was performed to retrieve any reported adverse event associated with adjuvant use of dexmedetomidine and clonidine in local anesthesia from published literature up to 1 July 2020. Assessment of the quality of included studies was performed by the Jadad score. A comparison of any reported adverse event was made between interventions by pooling data from studies using a direct meta-analysis technique. Review Manager software was used for meta-analysis of the available data. Dichotomous outcomes were summarized as risk ratios. Results: From 121 articles retrieved from the search finally 14 articles including 1120 patients had eligibility criteria for including in the meta-analysis. No significant difference was observed between bradycardia/hypotension (OR=1.17; 95 % CI= 0.66-2.10; P=0.580; I2= 53.78 %, P=0.027), nausea/vomiting (OR=0.91; 95 % CI= 0.59-1.42; P=0.706; I2= 0.0 %, P=0.940) dizziness/headache (OR=1.10; 95 % CI= 0.44-2.75; P=0.831; I2= 0.0 %, P=0.882) shivering(OR=0.95 % CI= 0.50-1.66; P=0.831; I2= 0.0 %, P=0.920) and dry mouth (OR=1.00; 95 % CI= 0.50-1.96; P=0.996; I2= 0.0 %, P=0.900). Conclusion: There is no difference in adverse events associated with the adjuvant use of dexmedetomidine and clonidine in local anesthesia.